Saúde organizacional, ética e confiança : o teste de um modelo preditivo a partir da percepção dos empregados - Fernandes, Marília Nunes (2008)
The interest in studies about organizational health started around the 1950s as a way to answer criticism about the organizational effectiveness construct; the purpose was to integrate attributes regarding the nature of the organizational system. The researchers who had proposed several theoretical models were not, however, concerned with testing them empirically. Therefore, the aim of this study was to test one model which examined the impact not only of the perception of ethical and organizational behaviours but also of the employees trust in the organization in relation to their perception of organizational health. In order to do so, 150 employees of companies in the Brazilian region of Triângulo Mineiro answered a questionnaire containing valid and consistent measures of the constructs. The data underwent descriptive and stepwise multiple regression analysis. For the first organizational health perception factor, entitled people and team integration , the following predictors were identified: system management , ethical standards , norms related to employees dismissal , and financial organizational recognition which, as a whole, explained 50% of the criteria-variable variance. For the second factor, called external demand adaptability and flexibility , the predictors found were: system management , promoting employees growth , and financial organizational recognition ; being them responsible altogether for 46% of the explanation of the criteria-variable variance. These results were discussed in conformity with the theory regarding the constructs. The limitations of this study were also pointed out, as well as the proposal of a research agenda.